ANALISA SINYAL RIPPLE PADA FENOMENA GIBBS : Analisa Sinyal Ripple pada Fenomena GIBBS - Mandela, Nelson; Gresia, Celsia; Wahdana; Azman, Muhammad; Hafidha, Nurul; Dewantoro, Armando (J-Eltrik, 2024)
The frequency domain is a method of analyzing signals based on their frequencies rather than time. A time-domain graph shows how a signal changes over time, while the frequency domain shows the frequency content and amplitude of each component. The Fourier Transform is used to convert a signal from the time domain to the frequency domain, while the inverse transform converts it back. The frequency spectrum displays the amplitude and phase of each frequency component of the signal. This analysis is important in fields such as physics, electronics, control systems, and statistics. Some techniques also combine the time and frequency domains to analyze signals that vary over time.